Concomitant 1q42.13-q44 Duplication and 14q32.33 Deletion: A Case Report and Review of Literature - Xu, PhD, Fang; Wei, BS, Fengxiang; Grommisch, BSc, Brittany; Zhang, PhD, MD, Hui Z; Li, PhD, Peining (North American Journal of Medicine and Science, 2017)
Duplications of 1q concomitant with other chromosomal deletions are rare conditions in association with compound phenotypes. We present a case with a duplication of 1q42.13-q44 and a deletion at 14q32.33 and perform a comprehensive review on relevant cases of simple or concomitant duplications involving distal 1q42-qter region. The patient was a 1-year-old boy with delayed mental development, relative macrocephaly, brain and facial deformities, hypotonia, and minor dilation of ascending aorta. Cytogenomic analyses revealed a derivative chromosome 14 with a 21.4 Mb duplication of 1q42.13-q44 and a 2.8 Mb deletion at 14q32.33. This derivative chromosome was inherited from his mother who is a carrier of a balanced translocation between 1q42.13 and 14q32.33. This patient presents compound phenotypes from the distal 1q42 duplication and 14q32.3 terminal deletion. Review of reported cases with duplications of 1q42-qter revealed that approximately 22% were de novo cases and 78% were familial cases from a maternal or a paternal carrier of a balanced translocation. Pedigrees from familial carriers of a balanced translocation involving 1q42 showed an increased risk up to 35% for spontaneous abortion. Thorough clinical assessment of compound phenotypes and follow up study on both parents are recommended for cases with concomitant 1q42-qter duplication and other chromosomal deletions. [N A J Med Sci. 2017;10(2):56-60. DOI: 10.7156/najms.2017.1002056]